1980
DOI: 10.1007/bf00500307
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of 7-ethoxycoumarin in primary maintenance cultures of adult rat hepatocytes

Abstract: 7-Ethoxycoumarin is metabolized to 7-hydroxycoumarin in short-term (1-4 days) maintenance cultures of adult rat hepatocytes. The 7-hydroxycoumarin is predominantly found as the sulphate and glucuronic acid conjugates. This pattern of metabolism is very similar to that observed with freshly-isolated rat hepatocytes and suggests that the culture system may be of value in studying the metabolism of novel chemicals designed for human therapeutic use. The specific activity of microsomal monooxygenase activity falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although earlier the same conclusion was made by Ullrich and Weber (1972) and by Aitio (1978) for microsomal preparations, the substrate has been added very often in organic solvent. Dimethylformamide has been used for hepatocyte cultures (Fry and Bridges 1980) and for isolated hepatocytes (Paterson et al 1984); methanol has been added to microsomal preparations (Boobis et al 1981, Paterson et al 1984 and to lOOOOg supernatant (Greenlee and Poland 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier the same conclusion was made by Ullrich and Weber (1972) and by Aitio (1978) for microsomal preparations, the substrate has been added very often in organic solvent. Dimethylformamide has been used for hepatocyte cultures (Fry and Bridges 1980) and for isolated hepatocytes (Paterson et al 1984); methanol has been added to microsomal preparations (Boobis et al 1981, Paterson et al 1984 and to lOOOOg supernatant (Greenlee and Poland 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of 7-ethoxycoumarin has been widely studied in rat liver slices [12, 17], lung slices [16], skin strips [18], perfused intestinal loop [19], rat brain [20], and hepatocytes [21, 22]. It was reported that 7-hydroxycoumarin, coumarin-7-O-glucuronide, and coumarin-7-O-sulfate were identified in rat liver slices [12, 16, 17], lung [16], and skin [18].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that 7-hydroxycoumarin, coumarin-7-O-glucuronide, and coumarin-7-O-sulfate were identified in rat liver slices [12, 16, 17], lung [16], and skin [18]. Among them, coumarin-7-O-sulfate was a major conjugate [12, 16-18, 21], or had a comparable extent with coumarin-7-glucuronide in the intestine [19]. Only 7-hydroxycoumarin was identified in rat brain [20].…”
Section: Resultsmentioning
confidence: 99%
“…Sulphate and glucuronide 7‐HC conjugates were then de‐conjugated to free 7‐HC by the addition of 25 μl β‐glucuronidase H1 solution (2 mg/ml in 0.1 M acetate buffer, pH 4.5) to each well and incubation of plates at 37 °C for 120 min with gentle shaking. Total 7‐HC production (representing the sum of free 7‐HC and 7‐HC retrieved from de‐conjugation reactions) was then analysed using the principles described by Fry et al (23, 24) and modified by Donato et al (23, 24) for the use of 96‐well plates. Reductions in phase II conjugation activity did therefore not cause a decrease in total 7‐HC production as this reduction caused a corresponding increase in free‐HC and no change in total 7‐HC production from 7‐EC.…”
Section: Methodsmentioning
confidence: 99%